1984
DOI: 10.1113/jphysiol.1984.sp015202
|View full text |Cite
|
Sign up to set email alerts
|

Water flow across the walls of single muscle capillaries in the frog, Rana pipiens.

Abstract: SUMMARY1. Individual capillaries of the transilluminated frog muscle cutaneous pectoris were perfused with suspensions of human red cells in frog Ringer solution containing 1 g/dl bovine serum albumin. The modified Landis technique (Michel, Mason, Curry & Tooke, 1974) was used to measure hydraulic conductivities of the capillary wall. Sucrose osmotic reflexion coefficients of the capillary wall were measured in four capillaries when the superfusate contained 100 mM-sucrose. All experiments were made at 22-24 '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The value for Lp found in the present experiments is very much lower than that of other endothelia (3 % of that found for frog skeletal muscle and 0 4 % of that found for mesenteric microvessels, see (Curry & Froekjaer-Jensen, 1984). The value obtained in the present study is similar to that found in mammals (Fenstermacher & Johnson, 1967;Paulson, Hertz, Bolwig & Lassen, 1977) in which the whole brain microvasculature was assessed, and is compatible with many of the measurements for cell membranes.…”
Section: Assessment Of Techniquesupporting
confidence: 76%
“…The value for Lp found in the present experiments is very much lower than that of other endothelia (3 % of that found for frog skeletal muscle and 0 4 % of that found for mesenteric microvessels, see (Curry & Froekjaer-Jensen, 1984). The value obtained in the present study is similar to that found in mammals (Fenstermacher & Johnson, 1967;Paulson, Hertz, Bolwig & Lassen, 1977) in which the whole brain microvasculature was assessed, and is compatible with many of the measurements for cell membranes.…”
Section: Assessment Of Techniquesupporting
confidence: 76%
“…First, while a change of capillary volume does follow a change in P, this change is rapid and when P, is greater than 10 cmH2O it is usually complete within 1 s (Michel et al 1974;Mason, 1976;Michel, 1980;Curry & Fr0kjaer-Jensen, 1984). In our micro-occlusion experiment this initial rapid movement of the red cell flow markers was not used to estimate transcapillary fluid movement.…”
Section: Discussionmentioning
confidence: 99%
“…In order to have rapid initial perfusion of the capillary and yet measure fluid movements across the capillary wall at pressures of 10-15 cmH2O, the pressure applied to the pipette for the initial perfusion was set initially at 30-35 cmH2O and then dropped into the desired range by the turn of a tap connected to a second manometer maintained at the lower pressure. On lowering the pressure, the immediate movement of the red cells reflected a rapid reduction of volume of the capillary (compliance effect) but this was usually complete within 1-2 s (Michel et al 1974;Mason, 1976;Smaje & Swayne, 1983;Curry & Fr0kjaer-Jensen, 1984 It is worth noting that for BSA, oC estimated from the transient data has a value of 0-76 (S.E. of mean + 004) and from the steady-state data has a value of 0-75 (S.E.…”
Section: Measurements Offluid Filtration In Single Capillariesmentioning
confidence: 99%
“…Because hyperosmolarity may affect capillary permeability (Granger et al 1979;Rasio, Bendayan & Goresky, 1981;Friedman & DeRose, 1982; but cf. Theven, Xuan, Vallois, Syrota & Pocidalo, 1982;Curry & Frokjaer-Jensen, 1984), hyperosmolar perfusions were always performed last. Osmotic transients have been described for continuous capillaries (e.g.…”
Section: Model Of Trans-synovialflowmentioning
confidence: 99%